Penerapan Model Pembelajaran Kooperatif Tipe STAD Dalam Meningkatkan Hasil Belajar PAI - Nurhanim Nurhanim (JURNAL GLOBAL EDUKASI, 2021)
Abstract: This research was conducted in grade IV SD Negeri 018479 Air Joman Baru for the academic year 2019/2020, which amounted to 15 students. The research used was observation technique, test technique, and documentation study. This type of research is Classroom Action Research. The research was carried out for 2 cycles. Each cycle was carried out 2 meetings consisting of 4 stages, namely planning, action, observation, and reflection. The results of student learning in cycle I after applying the STAD type cooperative learning model were 6 students who thoroughly studied with 40% completeness and class average value which is obtained is still low is 55.93. Therefore, it was continued in the second cycle, there were 13 people who completed learning with 86.67% classical completeness and the class average value obtained was 80.15. After the action was carried out in cycle II, the student learning outcomes had reached classical completeness, then the action was stopped. Thus it can be concluded that the hypothesis which states that an increase in student learning outcomes can be improved through the STAD type cooperative learning model in the subject of Islamic Religious Education, the subject of knowing the book of Allah SWT in grade IV SD Negeri 018479 Air Joman Baru for the 2019/2020 academic year has been successful. Keywords: Learning Outcomes, Cooperative Learning Model Type STAD, Knowing the Book of Allah SWT.  Abstrak: Penelitian ini dilaksanakan di kelas IV SD Negeri 018479 Air Joman Baru Tahun Pelajaran 2019/2020 yang berjumlah 15 orang siswa. Penelitian yang digunakan adalah  tekhnik observasi, tekhnik tes, dan studi dokumentasi. Jenis penelitian ini adalah Penelitian Tindakan Kelas. Pelaksanaan penelitian dilaksanakan selama 2 siklus. Setiap siklus dilaksanakan 2 kali pertemuan yang terdiri 4 tahapan yaitu perencanaan, tindakan, pengamatan, dan refleksi.Hasil pembelajaran siswa pada siklus I setelah diterapkan model pembelajaran kooperatif tipe STAD  adalah 6 orang siswa yang tuntas belajar dengan ketuntasan 40% dan nilai rata-rata kelas yang diperoleh masih rendah adalah 55,93. Oleh karena itu dilanjutkan pada siklus II adalah 13 orang yang tuntas belajar dengan ketuntasan klasikal 86,67% dan nilai-rata-rata kelas diperoleh adalah 80,15. Setelah dilakukan tindakan pada siklus II hasil belajar siswa sudah mencapai ketuntasan klasikal, maka tindakan dihentikan. Dengan demikian dapat disimpulkan bahwa hipotesis yang menyatakan peningkatan hasil belajar siswa dapat ditingkatkan melalui model pembelajaran kooperatif tipe STAD dalam mata pelajaran Pendidikan Agama Islam materi mengenal kitab Allah SWT di kelas IV SD Negeri 018479 Air Joman Baru Tahun Pelajaran 2019/2020 telah berhasil. Kata Kunci: STAD, Kitab Allah SWT